Entrepreneurial orientation and internationalisation: a focus on firms in Sub-Saharan Africa - Baker, Ntokozo Aaron (My University, 2015)
This report is based on the influence of individual entrepreneurial orientation dimensions on internationalisation outcomes of firms in Sub-Saharan Africa. The study followed a positivist paradigm and was grounded on the multidimensional conceptualisation of entrepreneurial orientation and the contingency framework thereof by Dess and Lumpkin (1996). Computer-aided text analysis was employed to deduce the level of entrepreneurial orientation dimensions from the executive management’s review in the companies’ annual reports. Multiple regression techniques were used to test the relationship between each independent variable (innovativeness, proactiveness and risk taking) and the dependent variables (international scale and international scope). In addition, the role of contextual moderators (economic development, home market size, political stability and regulatory quality) on each of these relationships was investigated. The target population was small to medium sized enterprises with more than 42 months of business activity and an established growth trajectory. The sampling frame included firms that were listed on the Botswana, Nairobi (Kenya), Nigerian, Johannesburg Securities Exchange’s AltX (South Africa), and Zimbabwean securities exchange markets. The final sample was made up of 124 exchange-listed firms with a market capitalisation of below R3 billion. The majority of the hypotheses were not supported by the findings. Innovativeness, proactiveness and risk taking were not significantly related to the scale and scope of internationalisation. In addition, the macroeconomic factors were not significant moderators of entrepreneurial orientation dimensions versus the scale and scope of internationalisaton. However, the U-shaped relationship between risk taking and international scope was stronger when the level of regulatory quality was high. Furthermore, the technology industry was associated with greater international scope. The overall findings contributed to the understanding of the scale and scope of internationalisation
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.